Efektivitas Bimbingan Kelompok Teknik Modelling Simbolis untuk Meningkatkan Efikasi Diri Siswa IX SMP Negeri 3 Baubau - Rasman Sastra Wijaya; Unhaluddin Thalib Kurniawan; Risma Irmayana (Psychocentrum Review, 2020)
The purpose of this study was to examine the effectiveness of group counseling services for effective symbolic modeling techniques to improve the self-efficacy of class IX students of SMP Negeri 3 Baubau. The experimental design used in this study was a one-group pretest and posttest design. The population in this study were 72 class IX students of SMP Negeri 3 Baubau, totaling 72 people consisting of 3 classes. The sample in this study was grade IX students of SMP Negeri 3 Baubau who had low self-efficacy as many as 13 students who were used as a sample of a treatment effectiveness test. Testing the validity of the self-efficacy scale using the Analyze Correlate Bivariate test through the help of a computer program statistics product and service solution (SPSS) 16.0 for windows. Known value of Z -3,185 with Asymp. Sig (2-tailed) value of 0.001 in this study is smaller than ˂ 0.05, it can be concluded that the Guidance Services Group of symbolic modeling techniques is effective to improve the self-efficacy of class IX students of SMP Negeri 3 Baubau which is done successfully significantly or effectively to be carried out , this means, the hypothesis is accepted